Rancang Bangun Pendeteksi Pengaman Pintu Dan Jendela Berbasis Internet Of Things (IoT) - Sujono, Sujono; Herlambang, Wahyu Ady (Exact Papers in Compilation (EPiC), 2021)
Home security is very important and always desired by every home owner. One of the problems that threaten the security of home owners is theft. From this statement, it is necessary to have an innovation which of these innovations can help increase home security. This innovation is in the form of monitoring the open and closed doors. This monitoring has the function of providing information that occurs in the house. The Internet of Things (IoT) enables devices to communicate such as sending and receiving data. This research was conducted to prevent crimes such as theft, so that the house will remain safe if the owner is at home or outside the house. This research designed the open and closed door and window detectors consisting of the esp8266 nodemCU module, buzzer and magnetic sensor, blynk. The blynk application is able to provide realtime information to users, so that it can monitor the state of doors and windows and can inform when someone opens doors and windows forcibly. When the door is opened the magnetic sensor will have logic 0 and esp8266 provides information on sensor data that is sent to blynk, then the data is accessed with the blynk application as a user interface display. The steps taken in this study were first functional and nonfunctional analyzing, then the results of the analysis were designed and then coded using the Arduino IDE. Next the tool is tested whether it is functioning properly or not, if it is deemed to be functioning properly, the tool is ready to be applied. The resulting tool can send notifications of opening and closing doors and windows on a smartphone.